PENGEMBANGAN EKONOMI KREATIF DESA MELALUI BADAN USAHA MILIK DESA (BUMDES) MENUJU KOPERASI BERBASIS IT - HENDRO WIBOWO (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The allocation of funds for villages from year to year has increased; the Government allocates Funds in 2015 amounting to Rp. 20 Trillion, in 2016 of Rp. 47 trillion, and in 2017 to Rp. 60 trillion. For the province of Banten in 2015 get funding of Rp. 200 billion, in 2016 to Rp. 791 Billion, and in the year 2017 of Rp. 1 trillion. This Village Fund requires financial management accountability (planning, implementation, administration, reporting, accountability, coaching and financial control). The purpose of the Fund's allocation is to establish a